Oksana Sarkisova, Péter Apor (edd.), Past for the Eyes: East European Representations of Communism in Cinema and Museum after 1989: Budapest 2008, Central European University Press, 416 s. - Roubal, Petr (Dějiny – teorie – kritika, 2009)
Review.